Finland's Public Sector Balance Sheet : A Novel Approach to Analysis of Public Finance - Brede, Maren; Henn, Christian (Washington, D.C. : International Monetary Fund, 2018)
We construct a comprehensive public sector balance sheet for Finland from 2000 to 2016 by complementing general government statistics with data on public corporations and public pensions. We show that exposure to valuation changes in equity markets through asset holdings and increases in pension liabilities relative to GDP amplify crisis impacts on public finances. We expand the balance sheet by including present value estimates of future fiscal flows; this allows us to perform fiscal stress tests and policy experiments. These analyses suggest that Finland's public finances will remain sound provided ongoing reform and consolidation efforts to address aging pressures are implemented as planned.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet